ELUCIDATION OF ADSORPTION PROPERTIES OF ZEOLITE 13X FOR CO₂ CAPTURE BY USING MOLECULAR SIMULATION APPROACH - RAZMAN, ALISSA NADIA (2023)
As the global concern over CO₂ gas emissions continues to escalate, the need for effective CO₂ capture technologies becomes more evident. Among various methods, adsorption is a promising approach for CO₂ capture and Zeolite 13X has been widely utilized as adsorbents.